Tinjauan Sistematis: Dampak Stigma terhadap Kesehatan Mental Tenaga Kesehatan yang Bekerja Selama Pandemi COVID-19 - Dila Widya Sambhara; Achmad Chusairi (Guidena)
COVID-19 pandemic has brought a lot of negative impacts for Healthcare Workers, one of the most essential roles in dealing with COVID-19 patients. One of the impacts is Healthcare Workers get negative stigmatization from the society. The stigma has impacts on Healthcare Workers’ mental health during the COVID-19 patient care. The purpose of this systematic literature review is to illustrate the impacts of stigma on COVID-19 Healthcare Workers’ mental health. Three scientific articles were found from three international journal databases, namely Google Scholar, Proquest and Sage, and also used in this systematic literature review, based on the suitability of the topic. Rigorous eligibility review was done using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) protocol. It can be inferred that there are several forms of impacts of stigma on Healthcare Workers’ mental health such as fatigue; stigma fear; anxiety; depression; trauma; burnout; the decrease of job satisfaction, psychological wellbeing, quality of life and coping function; feelings of being isolated and alienation; hesitating to ask for someone’s help; and the increase of alcohol use. This article can be used as a reference for future research related to the impact of stigma on COVID-19 Healthcare Workers’ mental health.